PENYIDIKAN TINDAK PIDANA PENIPUAN OLINE DIWILAYAH HUKUM KEPOLISIAN RESOR KOTA PEKANBARU - Ela Aprida Nafliana; Firdaus Firdaus; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Technological advancements both from information and communication are increasingly rapidlydeveloping which provide many conveniences for humanity. The internet is one product of technologicalprogress from information and means of communication. Many things can be done through the internetstarting from social relations, work, to doing business buying and selling online, you can directly contactother people. Online business, and e-banking services. The trade activities using the internet make the stateseem to be without territorial borders (bosdeles) to create benefits and convenience for a nation that can beseen in various forms of cooperation between countries in the fields of economy, politics and culture. Themechanism of transactions and agreements with the outside world is sufficiently controlled through smallspaces with internet protocol-based technology that offers effective, and modern facilities and other socialmedia that are connected to the internet.This research is sociological or empirical research, namely the type of research that uses communityassumptions in looking for facts that occur in the field to answer an existing problem. This research wascarried out in the Riau High Prosecutor's jurisdiction. While the population and sample are parties relatedto the problems examined in this study, the data sources used, primary data, secondary data, and tertiarydata. The technique of collecting data in this study was through interviews and literature review.From the results of the research that the authors did can be concluded, the first occurrence of online/ electronic media deprivation is influenced by various factors including law enforcement officials, facilitiesand infrastructure and the community. The community is divided into other fields of factors, namelyeconomic, environmental, socio-cultural, easy to carry out these crimes and because people are easilyfooled by power. Second Investigation of crimes against perpetrators of fraud carried out online by thePekanbaru City Police Department has not been maximally proven with the absence of cases of criminalacts of fraud through online being resolved.Keywords: Investigation - Crime - Online Fraud.